Method for calcining ardealite combination

Through the phosphogypsum segmented combined calcination method, the problems of insufficient quality of phosphogypsum products and the inability to flexible adjustment of the process are solved, and the utilization of high-value-added phosphogypsum is realized, and high-quality β gypsum powder and anhydrous type II gypsum fillers are produced. Meets a variety of application needs and enhances market competitiveness.

CN119118548APending Publication Date: 2024-12-13YIDU XINGFA CHEMICAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411086074.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize phosphogypsum, resulting in insufficient product quality, unable to achieve high-value utilization of phosphogypsum, and the process cannot flexibly adjust the production structure and cannot meet the complex downstream application market demand.

Method used

Phosphogypsum calcination method is adopted, including wet grinding pretreatment, flotation, plate and frame filtration, water washing and decomposition, tube calcination and cyclone grading and other steps. High-quality β gypsum powder is prepared through multiple calcination and grading. and anhydrous type II gypsum fillers to achieve excellent product quality and flexibility in production organization.

Benefits of technology

It has achieved high added value utilization of phosphogypsum, produced high-quality beta gypsum powder and anhydrous type II gypsum fillers, improved the purity and whiteness of the product, met the various application needs such as decoration and fillers, and improved the market. Competitiveness.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for calcining ardealite in a segmented combined manner, which comprises the following steps: carrying out wet grinding pretreatment on fresh ardealite raw slag after clear water size mixing, and carrying out flotation impurity removal on wet grinding slurry; ardealite obtained through flotation is filtered, washed with water and filtered again, and purified ardealite powder is obtained; feeding the water-containing purified ardealite powder to a tubular calcining kiln, and sequentially preheating, drying and calcining to obtain semi-hydrated gypsum powder; grinding the semi-hydrated gypsum powder and then carrying out cyclone classification to obtain fine-grained powder and coarse-grained powder, or directly cooling and grinding to obtain high-quality beta gypsum powder; feeding the fine-fraction powder to a two-section tubular calcining kiln, continuing high-temperature calcining to obtain II-type anhydrous gypsum, and performing ultrafine grinding to obtain a filler; according to the method, the production organization is flexible and diverse, three different products including the high-quality beta gypsum powder, the beta gypsum powder and the type II anhydrous gypsum filler can be obtained, and the product quality is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of comprehensive utilization of phosphogypsum, and in particular to a method for combined calcination of phosphogypsum. Background Art

[0002] At present, the common way to utilize phosphogypsum in bulk is mainly to produce cement retarders, gypsum building materials, etc. Among them, cement retarders and low-end building materials such as gypsum mortar have serious homogeneous competition in application scenarios, and the added value of products is low. Although they can form large-scale applications, the competition is too fierce and high value cannot be achieved. Although products such as β-gypsum powder for decoration, gypsum powder for molds, and anhydrous gypsum fillers have high added value, they are subject to factors such as low whiteness of phosphogypsum, substandard product quality, low device start-up rate, and high production costs. Effective process technology has not yet been formed for promotion and application.

[0003] Publication No. CN117886526A provides a method for preparing type II anhydrous gypsum and building gypsum from phosphogypsum. This patent invention produces type II anhydrous gypsum, building gypsum and organic slag through particle size classification, wet crystallization and flotation purification. The purity of the produced type II anhydrous gypsum can reach more than 93%, and the whiteness is greater than 90%, which is a good filler raw material; the purity of the building gypsum is greater than 90%, and the whiteness is greater than 60%.

[0004] Publication No. CN116102273A provides a method for preparing phosphogypsum by pretreating waste phosphogypsum. By drying, screening and pretreating the phosphogypsum, the total phosphorus content in the phosphogypsum is significantly reduced, and the content of total phosphorus impurities in the phosphogypsum is controlled to be no more than 0.36%. The prepared phosphogypsum has low impurity content, good stability and high quality.

[0005] Publication No. CN118164696A provides a method for preparing phospho-gypsum powder by using phosphogypsum and the phospho-gypsum powder. The phosphogypsum is neutralized by using limestone to remove residual acidic substances (such as H3PO4, H2PO4-). At the same time, by wet grinding, water can dissolve soluble impurities in the phosphogypsum, such as soluble phosphorus (H3PO4, H2PO4-) and soluble fluorine (NaF); at the same time, organic matter in the phosphogypsum can also be taken out, so that the obtained phosphogypsum powder has fewer impurities and higher quality.

[0006] Patent No. CN113511829B discloses a method for preparing building gypsum powder from phosphogypsum. The method promotes the dissolution of phosphogypsum by heating and stirring, releasing impurities such as crystalline phosphorus and crystalline fluorine in the phosphogypsum. After recrystallization, the purity of the gypsum can be improved and the impurity content in the gypsum can be reduced. Then, through multi-stage cyclone separation, the impurities in the gypsum are separated and removed by utilizing the different particle sizes of the impurities in the gypsum to obtain high-purity gypsum. The gypsum only needs to be calcined at a relatively low temperature to obtain high-quality building gypsum powder.

[0007] A variety of patented technologies have been published for β-gypsum powder and anhydrous type II gypsum filler for phosphogypsum, but these methods still have the following problems: insufficient product quality and can only be used in low-end building materials such as gypsum mortar and low-end fillers, lacking market competitiveness and product added value. At the same time, most processes can only produce one product, cannot flexibly adjust production organization, and cannot cope with the complex downstream application market environment.

[0008] Therefore, finding a new method for preparing β-gypsum powder and anhydrous type II gypsum from phosphogypsum has become a difficult problem that needs to be solved urgently to achieve large-scale and high-value utilization of phosphogypsum. Summary of the invention

[0009] The purpose of the present invention is to provide a method for the segmented combined calcination of phosphogypsum. The method of the present invention has flexible and diverse production organizations, and can obtain three different products of high-quality β-gypsum powder, β-gypsum powder and type II anhydrous gypsum filler, which can realize the high added value utilization of phosphogypsum and has excellent product quality. 1. To achieve the above object, the technical solution adopted by the present invention includes the following steps: (1) adding water to the phosphogypsum slag to prepare slurry, and performing wet grinding pretreatment to obtain wet grinding slurry; (2) adding water to the wet grinding slurry and then adding flotation reagents to perform reverse flotation to obtain tailings and refined phosphogypsum slurry; (3) using a plate and frame filter to separate the solid and liquid of the refined phosphogypsum slurry to obtain refined phosphogypsum; (4) adding water to the refined phosphogypsum slurry to make slurry again, washing and removing impurities, and then using a plate and frame filter to separate the solid and liquid again, and then adjusting the pH of the washed phosphogypsum to obtain purified phosphogypsum; (5) sending the purified phosphogypsum powder to a tubular calcining kiln for heating and calcining to obtain hemihydrate gypsum powder; (6) The semi-hydrated gypsum powder is ground and then sent to a cyclone classifier for classification to obtain coarse-grained powder and fine-grained powder; or the semi-hydrated gypsum powder is directly ground to a suitable particle size and then prepared into high-performance β-gypsum powder.

[0010] (7) The fine-grained powder is sent to a two-stage tubular calcining kiln for heating and calcining to obtain type II anhydrous gypsum, which is then ultra-finely ground to obtain filler; (8) The coarse-grained powder is cooled and ground into a suitable particle size to prepare β-gypsum powder.

[0011] The preferred step (1) is that the calcium sulfate dihydrate content of the phosphogypsum slag is 80-90%, the whiteness is 25-30%, the pulping concentration is 50%-60%, and the grinding is carried out in a ceramic ball mill for 5-10 minutes.

[0012] Preferably, in step (2), the wet grinding slurry concentration after slurry adjustment is 30-40%, and the flotation reagents are a decolorizing collector and an impurity removing collector, wherein the decolorizing collector is a mixture of pine oil, diesel, and ethyl ether alcohol in a mass ratio of 2-5:3-6:0-3; the impurity removing collector is a mixture of palmitic acid, stearic acid, oleic acid, and linoleic acid in a mass ratio of 20-25:5-10:12-25:40-55, and then saponified to obtain a mixed fatty acid sodium salt, and the obtained mixed fatty acid sodium salt is mixed with methyl isopropyl carbinol in a mass ratio of 7-8:2-3 to prepare a composite mixture. The reverse flotation is a one-rough, two-fine and one-sweep process, and its process is: add 0.1-0.2kg / t of decolorizing collector and 0.3-0.4kg / t of impurity collector to the wet grinding slurry in sequence, and then carry out roughing to obtain roughing concentrate and foam product I, add 0.1-0.2kg / t of decolorizing collector and 0.2-0.3kg / t of impurity collector to the obtained roughing concentrate, and carry out one-time concentrating to obtain concentrating I concentrate and foam product II, add 0.1-0.2kg / t of decolorizing collector and 0.2-0.3kg / t of impurity collector to the obtained concentrating I concentrate, and carry out two-time concentrating to obtain final concentrate and foam product III, mix foam product I, foam product II and foam product III for scavenging operation, and obtain scavenging concentrate and final tailings, and the scavenging concentrate is returned to the roughing. The whiteness of the refined phosphogypsum should reach more than 65% after drying at 45°C.

[0013] Preferably, the water slurry concentration in step (4) is 35-45%, and the pH value is adjusted to 4.5-5.5 using CaO. The purified phosphogypsum has a water-soluble phosphorus content of ≤0.1%, a water-soluble fluorine content of ≤0.1%, and a pH value of ≥4.5. Preferably, the calcining kiln temperature in step (5) is 150-180°C.

[0014] Preferably, in step (6), the grinding is performed by dry grinding with a ceramic ball mill for 5 to 15 minutes. After cyclone classification, the coarse particle size is 0.038 to 0.074 mm or larger, and the fine particle size is 0.038 to 0.074 mm or less.

[0015] Preferably, the temperature of the second-stage calcining kiln in step (7) is 700-800°C, and the ultrafine grinding is performed by Raymond mill.

[0016] Preferably, the grinding in step (8) and step (6) is performed by ball milling.

[0017] The method for staged combined calcination of phosphogypsum provided by the present invention has the following advantages: firstly, after the phosphogypsum is repulped and ball-milled, the eutectic phosphorus in the phosphogypsum and the organic impurities contained in the crystals can be fully released, the organic impurity removal effect of the phosphogypsum flotation can be enhanced, the phosphorus and fluorine impurity content of the phosphogypsum after water washing and modification can be reduced, and the quality of the raw materials can be improved; secondly, the method of combined calcination in two stages of kilns can realize flexible control of multiple products, realize the production of high-performance β gypsum powder for decorative and renovating building materials, and the β building gypsum powder for plaster mortar, gypsum board and other building materials, and high High-performance anhydrous type II gypsum is used in filler fields such as plastics and rubber; thirdly, the gypsum loses water after calcination, cracks appear in the crystals, and the hardness decreases, while the impurity crystals such as quartz in phosphogypsum have not changed and are relatively hard. Selective crushing can be achieved through ball milling and dry grinding, that is, gypsum is crushed first and the particle size is finer. After cyclone classification, the gypsum can be purified and impurities removed, and the purity and whiteness are further improved. This part of the product is separated to make high-performance anhydrous type II gypsum filler to increase added value, and the remaining poor quality β gypsum powder can be used for low-end gypsum building materials. Specific implementation plan Example 1 Processing of phosphogypsum from a phosphorus chemical company (purity of calcium sulfate dihydrate 85%, whiteness 31%, total phosphorus 2.1%, water-soluble phosphorus 0.5%, water-soluble fluorine 0.3%, pH 2.5).

[0019] The decolorizing collector is a mixture of pine oil, diesel and ethyl ether alcohol in a mass ratio of 3:5:2; the impurity removing collector is a mixture of palmitic acid, stearic acid, oleic acid and linoleic acid in a mass ratio of 20:5:25:50, which is then saponified to obtain a mixed fatty acid sodium salt, and the obtained mixed fatty acid sodium salt is mixed with methyl isopropyl carbinol in a mass ratio of 8:2 to prepare a composite mixture.

[0020] (1) Add water to the phosphogypsum slag to prepare a slurry with a concentration of 55%, and wet-grind it in a ceramic ball mill for 7 minutes to obtain a wet-grinded slurry; (2) After adding water to the wet grinding slurry to adjust the slurry to 35%, 0.2 kg / t of decolorizing collector and 0.4 kg / t of impurity collector are added in sequence for roughing to obtain a roughing concentrate and a foam product I. 0.1 kg / t of decolorizing collector and 0.25 kg / t of impurity collector are added to the obtained roughing concentrate for primary concentration to obtain a concentrated concentrate I concentrate and a foam product II. 0.1 kg / t of decolorizing collector and 0.2 kg / t of impurity collector are added to the obtained concentrated concentrate I for secondary concentration to obtain a refined phosphogypsum slurry and a foam product III. The foam products I, II and III are mixed for scavenging to obtain a scavenged concentrate and final tailings. The scavenged concentrate is returned to the roughing; (3) using a plate and frame filter to separate the solid and liquid of the refined phosphogypsum slurry to obtain refined phosphogypsum; (4) adding water to the refined phosphogypsum slurry to adjust the concentration to 40%, performing solid-liquid separation again using a plate and frame filter, and then adding CaO to adjust the pH value of the washed phosphogypsum to 4.5 to obtain purified phosphogypsum; (5) Sending the purified phosphogypsum powder to a tubular calcining kiln for heating and calcining, and controlling the temperature at 165°C to obtain hemihydrate gypsum powder; (6) The semi-hydrated gypsum powder is dry-ground using a ceramic ball mill for 7 minutes. After grinding, it is sent to a cyclone classifier for classification to obtain coarse-grained powder with a particle size of more than 0.043 mm and fine-grained powder with a particle size of less than 0.043 mm.

[0021] (7) The fine-grained powder obtained by classification is sent to a two-stage tubular calcining kiln for heating and calcining at a controlled temperature of 700°C to obtain type II anhydrous gypsum, which is then subjected to ultrafine grinding to obtain filler; (8) The coarse-grained powder obtained by classification is cooled and ground into a suitable particle size to prepare β-gypsum powder.

[0022] The purified phosphogypsum obtained in this embodiment has a purity of 94%, a whiteness of 68%, a water-soluble phosphorus content of 0.08%, and a water-soluble fluorine content of 0.03%. The high-performance β-gypsum powder obtained by direct grinding without classification has a whiteness of 86%, a 2h flexural strength of 3.7 MPa, a 2h compressive strength of 8.3 MPa, an initial setting time of 8 min, and a final setting time of 15 min, which meets the quality requirements of special-grade gypsum powder for ceramic molds and gypsum powder for decoration and renovation; the anhydrous type II gypsum filler obtained after classification has a whiteness of 95.4%, a purity of 98.2%, and a yield of 60%. The β-gypsum powder obtained has a whiteness of 74%, a purity of 87.7%, a 2h flexural strength of 3.0 MPa, a 2h compressive strength of 6.1 MPa, an initial setting time of 5 min, and a final setting time of 16 min, which meets the 3.0 standard for building gypsum.

[0023] Comparative Example 1 The method and steps are the same as those in Example 1, except that grinding treatment is not performed in step (1). The purified phosphogypsum obtained in this example has a purity of 90%, a whiteness of 61%, a water-soluble phosphorus of 0.15%, and a water-soluble fluorine of 0.09%. The whiteness and water-soluble phosphorus content of the purified phosphogypsum do not meet the requirements. After being used in the production of subsequent products, the whiteness of the product is low. The whiteness of the high-performance β-gypsum powder is 78%, which can only meet the requirements of qualified gypsum powder for decoration and renovation, and has a low added value. The main reason for this is that without grinding treatment, impurities such as eutectic phosphorus and organic matter in the gypsum cannot be released, which affects the flotation decolorization and impurity removal effect, and the obtained purified phosphogypsum has insufficient whiteness and purity.

[0024] Comparative Example 2 The method and steps are the same as those in Example 1, except that step (4) is not subjected to CaO treatment for adjusting pH. The purified phosphogypsum obtained in this example has a purity of 93.4%, a whiteness of 67%, a water-soluble phosphorus content of 0.32%, and a water-soluble fluorine content of 0.18%. The water-soluble phosphorus and fluorine of the purified phosphogypsum do not meet the standards. The high-performance β-gypsum powder obtained by direct grinding without classification has a whiteness of 84.6%, a 2h flexural strength of 2.4 MPa, a 2h compressive strength of 5.5 MPa, an initial setting time of 11 min, and a final setting time of 23 min, which only meets the requirements for qualified products of gypsum powder for decoration and renovation, and the added value is low. This is because a simple water washing operation cannot obtain the water-soluble phosphorus and fluorine content that meets the requirements, resulting in the high-performance β-gypsum powder having a whiteness that meets the standards, but a strength that only meets the requirements for qualified products.

[0025] Comparative Example 3 The method and steps are the same as those in Example 1, except that step (6) is directly classified by cyclone without dry grinding. The purified phosphogypsum obtained in this example has a purity of 93.5%, a whiteness of 67.8%, a water-soluble phosphorus content of 0.09%, and a water-soluble fluorine content of 0.02%. The quality of the high-performance β-gypsum powder obtained by direct grinding without classification is consistent with that of Example 1, and meets the quality requirements of gypsum powder for ceramic molds and gypsum powder for decoration and renovation. The anhydrous type II gypsum filler obtained after classification has a whiteness of 95.4%, a purity of 97.9%, and a yield of 47.7%. The obtained β-gypsum powder has a whiteness of 80.4%, a purity of 89.49%, a 2h flexural strength of 3.4Mpa, a 2h compressive strength of 6.5Mpa, an initial setting time of 5min, and a final setting time of 17min. The yield of the obtained anhydrous type II gypsum filler is low, and the quality of the β-gypsum powder is excessive, which is not conducive to the high added value utilization of the product.

[0026] Comparative Example 4 The method and steps are the same as those in Example 1, except that step (6) is not subjected to post-dry grinding classification. The purified phosphogypsum obtained in this example has a purity of 93.7%, a whiteness of 68.1%, a water-soluble phosphorus content of 0.08%, and a water-soluble fluorine content of 0.02%. The quality of the obtained high-performance β-gypsum powder is consistent with that in Example 1, and meets the quality requirements of gypsum powder for ceramic molds and gypsum powder for decoration and renovation. The anhydrous type II gypsum filler obtained after classification has a whiteness of 90.4% and a purity of 93.8%. The whiteness and purity of the anhydrous type II gypsum filler are relatively low (taking light calcium as a reference, the minimum whiteness requirement in the fields of papermaking, plastics, etc. is above 92%).

[0027] Comparative Example 5 The method and steps are the same as those in Example 1, except that the grading particle size in step (6) is changed to 0.038 mm. The purified phosphogypsum obtained in this example has a purity of 93.3%, a whiteness of 67.1%, a water-soluble phosphorus content of 0.09%, and a water-soluble fluorine content of 0.03%. The performance of the obtained high-performance β-gypsum powder is consistent with that of Example 1, and meets the quality requirements of the special-grade gypsum powder for ceramic molds and decorative gypsum powder; the anhydrous type II gypsum filler obtained after grading has a whiteness of 95.7%, a purity of 98.9%, and a yield of 45.5%. The obtained β-gypsum powder has a whiteness of 79.1%, a purity of 88.62%, a 2h flexural strength of 3.3 Mpa, a 2h compressive strength of 6.6 Mpa, an initial setting time of 7 min, and a final setting time of 16 min. The yield of the obtained anhydrous type II gypsum filler is low, and the quality of the β-gypsum powder is excessive, which is not conducive to the high added value utilization of the product.

[0028] Comparative Example 6 The method and steps are the same as those in Example 1, except that the grading particle size in step (6) is changed to 0.074 mm. The purified phosphogypsum obtained in this example has a purity of 94.1%, a whiteness of 68.2%, a water-soluble phosphorus content of 0.08%, and a water-soluble fluorine content of 0.02%. The performance of the obtained high-performance β-gypsum powder is consistent with that of Example 1, and meets the quality requirements of gypsum powder for ceramic molds and gypsum powder for decoration and renovation. The anhydrous type II gypsum filler obtained after grading has a whiteness of 91.1%, a purity of 95.6%, and a yield of 51%. The obtained β-gypsum powder has a whiteness of 82%, a purity of 91.31%, a 2h flexural strength of 3.5 MPa, a 2h compressive strength of 6.8 MPa, an initial setting time of 6 min, and a final setting time of 15 min, meeting the building gypsum 3.0 standard. The whiteness and purity of the anhydrous type II gypsum filler are relatively low (taking light calcium as a reference, the minimum whiteness requirement in the fields of papermaking, plastics, etc. is above 92%).

[0029] The above description is only a preferred embodiment of the present invention, and is not intended to limit the implementation scheme. It should be noted that it is possible for a person skilled in the art to make several improvements and changes without departing from the creative concept of the present invention, and these all fall within the scope of protection of the present invention.

Claims

1. A method for calcining phosphogypsum in stages, characterized in that: The following steps are involved: (1) Adding water to the phosphogypsum slag to prepare slurry, and performing wet grinding pretreatment to obtain wet grinding slurry; (2) adding water to the wet grinding slurry and then adding flotation reagents to perform reverse flotation to obtain tailings and refined phosphogypsum slurry; (3) using a plate and frame filter to separate the solid and liquid of the refined phosphogypsum slurry to obtain refined phosphogypsum; (4) adding water to the refined phosphogypsum slurry to make slurry again, washing and removing impurities, and then using a plate and frame filter to separate the solid and liquid again, and then adjusting the pH of the washed phosphogypsum to obtain purified phosphogypsum; (5) sending the purified phosphogypsum powder to a tubular calcining kiln for heating and calcining to obtain hemihydrate gypsum powder; (6) Grinding the semi-hydrated gypsum powder and sending it to a cyclone classifier for classification to obtain coarse-grained powder and fine-grained powder; Alternatively, the semi-hydrated gypsum powder is directly ground to a suitable particle size to prepare high-performance β-gypsum powder; (7) The fine-grained powder is sent to a two-stage tubular calcining kiln for heating and calcining to obtain type II anhydrous gypsum, which is then ultra-finely ground to obtain filler; (8) The coarse-grained powder is cooled and ground into a suitable particle size to prepare β-gypsum powder.

2. The method for staged combined calcination of phosphogypsum according to claim 1, characterized in that: In the step (1), the calcium sulfate dihydrate content of the phosphogypsum slag is 80-90%, the whiteness is 25-30%, the pulping concentration is 50-60%, and the grinding is carried out in a ceramic ball mill for 5-10 minutes.

3. The method for staged combined calcination of phosphogypsum according to claim 1, characterized in that: The wet grinding slurry concentration after slurry adjustment in step (2) is 30-40%, and the flotation reagents are a decolorizing collector and an impurity removing collector, wherein the decolorizing collector is a mixture of pine oil, diesel, and ethyl ether alcohol in a mass ratio of 2-5:3-6:0-3; the impurity removing collector is a mixture of palmitic acid, stearic acid, oleic acid, and linoleic acid in a mass ratio of 20-25:5-10:12-25:40-55, and then saponified to obtain a mixed fatty acid sodium salt, and the obtained mixed fatty acid sodium salt is mixed with methyl isopropyl carbinol in a mass ratio of 7-8:2-3 to prepare a composite mixture.

4. The method for staged combined calcination of phosphogypsum according to claim 3, characterized in that: The reverse flotation in step (2) is a one-roughing, two-fines and one-scavenging process, and its process is as follows: 0.1-0.2 kg / t of decolorizing collector and 0.3-0.4 kg / t of impurity collector are sequentially added to the wet grinding slurry, and then roughing is performed to obtain a roughing concentrate and a foam product I; 0.1-0.2 kg / t of decolorizing collector and 0.2-0.3 kg / t of impurity collector are added to the obtained roughing concentrate, and a first concentration is performed to obtain a concentrated I concentrate and a foam product II; 0.1-0.2 kg / t of decolorizing collector and 0.2-0.3 kg / t of impurity collector are added to the obtained concentrated I concentrate, and a second concentration is performed to obtain a final concentrate and a foam product III; the foam products I, II and III are mixed and scavenged to obtain a scavenged concentrate and a final tailing; the scavenged concentrate is returned to the roughing.

5. The method for staged combined calcination of phosphogypsum according to claim 1, characterized in that: In the step (4), the water slurry concentration is 30-40%, and the pH value is adjusted to about 4.5-5.5 using CaO. The water-soluble phosphorus content of the purified phosphogypsum is ≤0.1%, the water-soluble fluorine content is ≤0.1%, and the pH value is ≥4.

5.

6. The method for staged combined calcination of phosphogypsum according to claim 1, characterized in that: The calcining kiln temperature in step (5) is 150-180°C.

7. The method for staged combined calcination of phosphogypsum according to claim 1, characterized in that: In the step (6), the grinding is carried out by dry grinding with a ceramic ball mill for 5 to 10 minutes. After cyclone classification, the coarse particle size is 0.038 to 0.074 mm or larger, and the fine particle size is 0.038 to 0.074 mm or smaller.

8. The method for staged combined calcination of phosphogypsum according to claim 1, characterized in that: The temperature of the second-stage calcining kiln in step (7) is 650-800° C., and the ultrafine grinding is performed by Raymond mill.

9. The method for staged combined calcination of phosphogypsum according to claim 1, characterized in that: In the step (8) and the step (6), the grinding is performed by ball milling.

Citation Information

Cited By

  • Method for whitening and removing impurities from solid waste phosphogypsum

    CN119972343A

  • Calcination preparation method of composite modified ardealite solid waste

    CN122403805A